ANALYTICAL STUDY OF RATE VOLUME LIQUID WATER CONTENT IN LOW CLOUDS OVER IRAQ - & et al., Zangana (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Iraq suffers a severe declining catastrophic in water resources; due to disagreement Share water to the neighboring countries Turkey, Syria and Iran. As well as the water policy in Iraq is unclear, the management of Iraq water have no strategic plan to treat the severe decrease in water sources. In this study, adopted eight climatic stations, are available at Iraqi general meteorological organization. The low clouds data 24 observations per day had been taken, from 1975 to 2005. For this purpose, the researchers determined the distribution of the stations and water amount at the Iraq using (GIS) Technique.  It has found the annual average liquid water content calculated from the Low cloud only is 2585742648 m3, and the annual average Rainfall from the low cloud is 2563537 m3. In addition, the net LWC is 2583179111 m3, so there are great opportunities to Enhancement rain from Low Clouds. To get the greatest benefit from the main low – level clouds in supplying liquid water for cloud seeding, must be given a serious attention to observing four clouds type (Sc5, Cb9, Sc8 and Cu2).